Explaining the Volume of Trade: An Eclectic Approach - Markusen, James R. (American Economic Review, 1986)
Divide the world into a capital-abundant North and a labor-abundant South. Subdivide the North into two identical regions, East and West. Modern trade theory predicts intra-industry trade in differentiated manufactured goods between East and West, and traditional interindustry trade based on factor endowments between North and South. The model I develop explains both the volume and the direction of trade by combining nonhomothetic preferences with scale economies and differences in endowments.